Optical studies of the surface effects from the luminescence of single GaN/InGaN nanorod light emitting diodes fabricated on a wafer scale - Chan, C; Reid, B; Taylor, R; Zhuang, Y; Shields, P; Allsopp, D; Jia, W (2013)
Time-resolved and time-integrated microphotoluminescence studies at 4.2 K were performed on a single InGaN/GaN nanorod light emitting diode, fabricated in an array, on a wafer scale by nanoimprint lithography. Emission properties and carrier dynamics of the single nanorods are presented. Sharp peaks of 2 meV line-width were observed. The single nanorods possess longer decay rates than an unprocessed wafer at delay-times above 50 ns after excitation. The time evolution of the photoluminescence spectra implies that the slower decay times are due to surface related localisation near the perimeter of the nanorods, resulting in a spatial separation of the recombining carriers at low excitation densities. © 2013 American Institute of Physics.